PROBLEM BASED LEARNING (PBL) MENGGUNAKAN PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH KIMIA SISWA - Ricardus Jundu; A. K. Prodjosantoso; Apolonia H. Ramda; Silfanus Jelatu (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
This study aims to investigate the learning effectiveness of the PBL model using a scientific approach in Indonesian current curriculum in the context of students’ problem-solving ability in chemistry, specifically in the problem of acid-base solution. This research is designed in a quasi-experiment using a nonequivalent control group design. There were 43 students divided in 2 classes used as the sample in this research. The experiment class 1 was taught by using the PBL learning model of scientific approach while the conventional learning that is usually used by chemistry teachers, is applied in experiment class 2. The finding of the research shows that the PBL learning model using a scientific approach in learning acid-base solutions is highly effective to promote students’ problem-solving.